Pembuatan Foodpedia Kuliner Khas Payakumbuh Berbasis Web - Harefti, Frisda Dini; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
In this paper discussed about the manufacture of foodpedia culinary typical web based Payakumbuh using wordpress, this application is used as a tool to facilitate users in finding the typical culinary information Payakumbuh. The research method used in this paper is descriptive method by describing the way of making the application and explain it in the form of narration. Based on the results of research Payakumbuh culinary foodpedia is making this process can be summarized as follows: 1) tracing information to the outlet souvenirs typical Payakumbuh namely Sanjai Rina and office KAN (Kerapatan Adat Nagari) Payakumbuh; 2) Payakumbuh typical culinary data collection collected based on the results of information searching from the source of information that is the outlet of the typical culinary Payakumbuh Sanjai Rina and office KAN (Kerapatan Adat Nagari) Payakumbuh; 3) the editing or checking process is done by completing the lack of writing the wrong word; 4) making web based foodpedia using wordpress, wordpress is a blog application; 5) design and design the application look, to make it look more interesting. Keywords: culinary, foodpedia, Payakumbuh